2008
DOI: 10.1111/j.1365-263x.2008.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal status of human primary teeth with physiological root resorption

Abstract: This investigation has revealed some changes in pulpal status of human primary teeth with physiological root resorption. These were not, however, as profound as one may have anticipated. It is therefore speculated that teeth could retain the potential for sensation, healing, and repair until advanced stages of root resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
1
30
0
4
Order By: Relevance
“…Similarly, previous study (13) comparing primary teeth with physiological root resorption and young permanent teeth, verified that histologically these dental groups are identical. It has been shown that primary teeth retain the potential for sensation, healing, and repair until reaching advanced stages of physiological root resorption (6). Such findings support the use of the pulp of third molar permanent teeth, with incomplete root formation, as a control group in this study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly, previous study (13) comparing primary teeth with physiological root resorption and young permanent teeth, verified that histologically these dental groups are identical. It has been shown that primary teeth retain the potential for sensation, healing, and repair until reaching advanced stages of physiological root resorption (6). Such findings support the use of the pulp of third molar permanent teeth, with incomplete root formation, as a control group in this study.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have focused on the occurrence of necrosis in dental tissues, but very few have dealt with apoptosis and its role in physiological root resorption of primary teeth (4)(5)(6)(7)20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulp is also eliminated by apoptosis during the process of physiological root resorption in primary teeth. However, the sequence of events and the definitive reason for the physiological death of pulp cells remain unclear (Monteiro et al, 2009).…”
Section: Other Cell Populationsmentioning
confidence: 99%
“…Furthermore, there is increasing basic science research to support the potential of the primary tooth pulp for healing and repair, even though it is a 'temporary' structure destined for physiological root resorption and exfoliation. 2 Many myths about the pain processing potential and inflammatory responses of the primary tooth have now been dispelled and treatments should strive to be much more biologically compatible.…”
Section: Bda Conferencementioning
confidence: 99%